(untitled) (Baghdad Science Journal, 2024)
A major global public health problem is the emergence of antimicrobial resistance to common commercial medications. Therefore, there is an urgent need for new antimicrobials with enhanced biological activity. In this regard , in this study 5 novel Quinolone derivative A, B, C, D, and E were synthesized and their structure was analyzed using UV light, FTIR, 1H NMR, and 13C NMR techniques. The structure of synthesized compounds was investigated. The well diffusion assay method was used to test the synthetic compounds’ antibacterial properties in vitro against two Gram-positive (Staphylococcus aureus and Streptococcus pyogenes) and two Gram-negative (Escherichia coli and Klebsiella pneumoniae) bacteria. Ciprofloxacin drug was used as an antibiotic standard. Best activity was shown by compound C against E. coli with an inhibition zone of 30mm and 33 mm at 250and 500 μg/mL respectively. While compound B in Staphylococcus aureus has high inhibition zone of 42mm and 47mm at 250and 500μg/mL respectively. However compound D in Klebsiella pneumoniae has high inhibition zone of 32mm and 35mm at 250 and 500μg/mL respectively, while compound A for Streptococcus pyogenes has inhibition zone of 45mm and 47mm at 250 and 500μg/mL respectively.